2015
DOI: 10.1371/journal.pone.0139462
|View full text |Cite
|
Sign up to set email alerts
|

Defense of Elevated Body Weight Setpoint in Diet-Induced Obese Rats on Low Energy Diet Is Mediated by Loss of Melanocortin Sensitivity in the Paraventricular Hypothalamic Nucleus

Abstract: Some animals and humans fed a high-energy diet (HED) are diet-resistant (DR), remaining as lean as individuals who were naïve to HED. Other individuals become obese during HED exposure and subsequently defend the obese weight (Diet-Induced Obesity- Defenders, DIO-D) even when subsequently maintained on a low-energy diet. We hypothesized that the body weight setpoint of the DIO-D phenotype resides in the hypothalamic paraventricular nucleus (PVN), where anorexigenic melanocortins, including melanotan II (MTII),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
2
6
0
2
Order By: Relevance
“…This effect was not observed under FSD conditions. Thus, findings suggest diminished melanocortin tone within the PVN of MORF1 males, and further support the notion that even under the CD conditions, these animals are primed for a metabolically adverse phenotype 42. Within the VTA, no differences in α-MSH were observed, demonstrating region-specific modifications in POMC-derived neuropeptide distribution.…”
supporting
confidence: 76%
“…This effect was not observed under FSD conditions. Thus, findings suggest diminished melanocortin tone within the PVN of MORF1 males, and further support the notion that even under the CD conditions, these animals are primed for a metabolically adverse phenotype 42. Within the VTA, no differences in α-MSH were observed, demonstrating region-specific modifications in POMC-derived neuropeptide distribution.…”
supporting
confidence: 76%
“…A recent trial demonstrated that carbohydrate restriction is more beneficial for patients with higher insulin levels [44]. This is consistent with insulin [57,58] influencing the so-called "set point" [59] of eating behavior and body weight regulation, in the same way that efficacious interventions such as drug therapy [60] and surgery [61] do but which calorie restriction in isolation can't [62]. Ketosis has been shown to attenuate the increases in ghrelin and appetite that occur with dietary restriction [63] and there is growing interest in the role of therapeutic ketosis in weight loss interventions [64].…”
Section: Putative Physiological Mechanismsmentioning
confidence: 73%
“…The reason for weight regain after successful weight loss is complex and likely multifactorial, with factors such as hypothalamic-mediated weight homeostasis, environmental and psychological variables, frequency of interactions with health care professionals, participation in exercise, and underlying genetic pre-dispositions of the patients themselves to obesity all playing potential roles ( 20 – 23 ). Studies in rats have confirmed a strong and persistent neuro-humoral response to caloric restriction that drives weight regain once ad libitum food intake is restored ( 24 ). These physiological counter-regulatory mechanisms to preserve energy balance are driven by genetic and epigenetic factors which lead to an imprinted obesogenic “memory” that prevents weight loss maintenance ( 25 ).…”
Section: Discussionmentioning
confidence: 99%